2018
DOI: 10.5539/ibr.v11n8p163
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Interpersonal Trust and Knowledge Sharing in Workplace: The Mediational Role of Prosocial Motives

Abstract: This study is different from the usual cases that testing the intuitive factor as rewarding that affects the employees' knowledge sharing. In this study, the focus shifts to concentrating on the emotional factors such as interpersonal trust and the prosocial motives. Empirical methods are used to test the hypotheses, and the results show that interpersonal trust affects employees' knowledge sharing significantly. Moreover, the prosocial motives have been evidenced that it moderately mediates the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In testing the direct effect, first, we found that social capital positively influences teacher candidates' creative teaching behavior. This finding corroborates a previous study conducted by Weixu et al which showed that social networks (such as social involvement, support, and cooperation from others) affect individual creativity [33]. In addition, these findings are also consistent with previous studies in the context of organizational behaviour [21; 48].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In testing the direct effect, first, we found that social capital positively influences teacher candidates' creative teaching behavior. This finding corroborates a previous study conducted by Weixu et al which showed that social networks (such as social involvement, support, and cooperation from others) affect individual creativity [33]. In addition, these findings are also consistent with previous studies in the context of organizational behaviour [21; 48].…”
Section: Discussionsupporting
confidence: 93%
“…Empirically, social capital is an important aspect of creativity [32]. Individual creativity is influenced by characteristics related to social networks, such as social involvement, support, and cooperation from others [33]. In addition, several studies have demonstrated a beneficial relationship between social capital and inventive or creative performance [21; 22].…”
Section: Literature Review Social Capital and Creative Teachingmentioning
confidence: 99%
“…The companies' role in transferring knowledge is to create a supportive organizational environment which facilitates interactions between employees, encourages one to share ideas and to create new solutions (Nonaka and Takeuchi, 1995). In the flow of knowledge, trust between employees and prosocial motives, which are aimed at taking care of the welfare of the general public and not only of the individual, play an important role (Ding, Choi, and Aoyama, 2018). Helping other employees and taking care of the common good of the company is therefore one of the foundations of knowledge-based organizations.…”
Section: Characteristics Of Knowledge-based Organizationsmentioning
confidence: 99%